Customer Satisfaction Levels at Logistics Operators: A Quantitative Study of Two Logistics Companies District of Middle Pomerania, Poland - Joanna Alicja DYCZKOWSKA; Marcin OLKIEWICZ (Communications of International Proceedings, 2024)
Logistics customer service is a key element in the selection of a logistics operator. To this end, a study of the level of customer satisfaction in the Polish area of two logistics operators was carried out. The aim of this article is to analyse and evaluate the level of logistics customer service and customer satisfaction in the two surveyed logistics companies in the area of Koszalin County. The main research problem is how logistics operators in the area of Koszalin County are perceived in comparison with other companies and how logistics customer service is assessed in the respective company. The research gap is the lack of assessment of the customer satisfaction level of logistics operators in rural areas. The research method was a diagnostic survey using a questionnaire technique, which was completed by customers of both companies in the area of Koszalin County, on the basis of which the customer satisfaction index (CSI) was calculated. The survey showed a good level of customer satisfaction (score 72.35 - 89.32%), which confirms the effectiveness of the current logistics solutions used by the logistics operators.
Keywords: logistics operators; customer; service; CSI